Aberrant timing and oddball detection in Schizophrenia: findings from a signed differential mapping meta-analysis. Issue 12 (December 2018) - Alústiza, Irene; Garcés, María Sol; Solanes, Aleix; Goena, Javier; Ortuño, Marta; Molero, Patricio; Radua, Joaquim; Ortuño, Felipe
Abstract: Schizophrenia (SZ) is associated with deficits in both temporal and salience processing. The underlying neurological dysfunctions in both processes, which are interrelated and share neuroanatomical bases, remain poorly understood. The principal objective of this study was to elucidate whether there are any brain regions that show abnormal response during timing and oddball tasks in patients with SZ. To this end, we conducted a signed differential mapping (SDM) meta-analysis of functional magnetic resonance imaging (fMRI) studies assessing abnormal responses elicited by tasks based on the oddball paradigm in patients with SZ. We conducted a similar SDM meta-analysis of neuroimaging studies of timing tasks in SZ. Finally, we undertook a multimodal meta-analysis to detect the common findings of the two previous meta-analyses. We found that SZ patients showed hypoactivation in cortical and subcortical areas related to timing. The dysfunction observed during timing tasks partially coincided with deficiencies in change-detection functions (particularly in the case of preattentional processing in the mismatch negativity response). We hypothesize that a dysfunctional timing/change detection network underlies the cognitive impairment observed in SZ.